2003
DOI: 10.1007/bf02411348
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric wafer active sensor embedded ultrasonics in beams and plates

Abstract: ABSTRACT-In this paper we present the results of a systematic theoretical and experimental investigation of the fundamental aspects of using piezoelectric wafer active sensors (PWASs) to achieve embedded ultrasonics in thin-gage beam and plate structures. This investigation opens the path for systematic application of PWASs for in situ health monitoring. After a comprehensive review of the literature, we present the principles of embedded PWASs and their interaction with the host structure. We give a brief rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 21 publications
0
71
0
Order By: Relevance
“…As suggested by Giurgiutiu,12 damage detection should be carried out at the centre frequency where the peak wave amplitude ratio between the S 0 mode and the A 0 mode is maximum.…”
Section: Selection Of Excitation Frequencymentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by Giurgiutiu,12 damage detection should be carried out at the centre frequency where the peak wave amplitude ratio between the S 0 mode and the A 0 mode is maximum.…”
Section: Selection Of Excitation Frequencymentioning
confidence: 99%
“…The study by Giurgiutiu,12 showed that when the diameter of PZT actuator is equal to odd integer multiples of half wavelength of the particular Lamb mode, strong voltage response for the corresponding Lamb mode will be produced; however, when the diameter of PZT actuator is equal to even integer multiples of half wavelength of Lamb modes, very weak voltage response will be generated.…”
Section: Selection Of Excitation Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…By using Lamb waves in a thin-wall structure, one can detect the existences and positions of cracks, corrosions, delaminations, and other damage [6]. Because of the physical, mechanical, and piezoelectric properties of PWAS transducers, they act as both transmitters and receivers of Lamb waves traveling in the plate.…”
Section: Eusr Steering Beam Direct Structural Imaging With Guidementioning
confidence: 99%